Opportunities and Limitations of Mobile Neuroimaging Technologies in Educational Neuroscience. Issue 4 (5th October 2021) - Janssen, Tieme W.P.; Grammer, Jennie K.; Bleichner, Martin G.; Bulgarelli, Chiara; Davidesco, Ido; Dikker, Suzanne; Jasińska, Kaja K.; Siugzdaite, Roma; Vassena, Eliana; Vatakis, Argiro; Zion‐Golumbic, Elana; van Atteveldt, Nienke
ABSTRACT: As the field of educational neuroscience continues to grow, questions have emerged regarding the ecological validity and applicability of this research to educational practice. Recent advances in mobile neuroimaging technologies have made it possible to conduct neuroscientific studies directly in naturalistic learning environments. We propose that embedding mobile neuroimaging research in a cycle (Matusz, Dikker, Huth, & Perrodin, 2019), involving lab‐based, seminaturalistic, and fully naturalistic experiments, is well suited for addressing educational questions. With this review, we take a cautious approach, by discussing the valuable insights that can be gained from mobile neuroimaging technology, including electroencephalography and functional near‐infrared spectroscopy, as well as the challenges posed by bringing neuroscientific methods into the classroom. Research paradigms used alongside mobile neuroimaging technology vary considerably. To illustrate this point, studies are discussed with increasingly naturalistic designs. We conclude with several ethical considerations that should be taken into account in this unique area of research. LAY ABSTRACT: Research on how the brain learns is typically done in a lab. Students perform a simplified learning task, alone, while their brain activity is recorded. However, this is a long way from learning in real complex classrooms with other students. In this article, we discuss innovations in mobile technology that allow investigating how brains learn in real classrooms, outside the lab. We also highlight recent studies that demonstrate how this approach may help in making research more relevant and useful for schools.